CIL II 4663 vs CIL II 4669: Story of a historiographic misunderstanding - Paredes Martín, Enrique (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
Roman milestones are one of the epigraphic typologies that, a priori, offer a simpler textual interpretation, given the continuous appearance in them of extremely repetitive and, therefore, well-known imperial titles. However, this repetition of practically identical texts in different pieces, added to the proliferation of many milestones of the same emperor in specific sections of a certain Roman road, has sometimes led to identification errors, false correspondences between different milestones and even duplicities in epigraphic research on the same milestone. In this study, through the analysis of the tradition that has been held about them since the 16th century, we will try to unravel these problems regarding two well-known milestones, coming from the Vía de la Plata, such as CIL II 4663 and CIL II 4669.